Design And Analysis of 3D Printable Prosthetic Foot with Honeycomb Structure - Kumarajati, Dhananjaya Yama Hudha (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2023)
This study designs and analyzes a 3D printable prosthetic foot with a honeycomb structure, which has many benefits for prosthetic foot design and analysis. The honeycomb structure can provide high strength and stiffness with low weight and material consumption, variable stiffness and damping properties, and biomimetic structure and function. This study uses 3D printing technology and finite element analysis (FEA) to design and fabricate the prosthetic foot and to evaluate its performance under different loading scenarios. The results show that the prosthetic foot has a satisfactory performance and meets the biomechanical requirements of the human foot. The results also show that 3D printing technology and FEA are reliable and valid tools for prosthetic foot design and analysis. This study contributes to the development of better and more affordable prosthetic feet and provides useful insights and guidelines for future research and practice.